Youth cultures as a perspective to analyze youths (1993-2018) - Feixa, Carles (Última Década, 2019)
This review article traces an overview of the studies on Latin American youth cultures over the past twenty-five years, from the 20th to the 21st century (from Generation X to Generation @), with a prologue in the Generation of Tribes and an epilogue in the Indignant Generation. From the pioneering studies on urban gangs and tribes to the most recent studies on transnational youth networks and cultures, youth cultural expressions offer a privileged perspective to analyze youths, their continuities, changes and contribution to the social, political and cultural evolution of Latin American societies as a whole.